Statistical and Economic Analysis of Uganda’s Tourism Expenditure and Motivation Survey 2019 - World Bank (World Bank, Washington, DC, 2020)
The Government of Uganda is keen on increasing the economic benefits derived from Uganda’s tourism assets. These assets include the national parks, the wildlife (a unique mixture of plains game and mountain gorillas), and landscapes for hiking, as well as water and adventure activities. Additional attractions include village visits, cultural assets, religious gatherings, and conference facilities. To support government policies aimed at increasing tourism benefits, this analysis is based upon an exit survey of visitors to Uganda in the 2019 high season for tourism. The Government of Uganda recognizes tourism’s potential and continues to prioritize tourism as one of the country’s growth sectors. To better understand the tourism development potential and monitor changes in tourism, two tourism expenditure and motivation survey (TEMS) were conducted in 2012 and 2019. Section one gives introduction. The report compares the two surveys through a statistical analysis in section two focused on the high season and an economic analysis centered on all of 2012 and 2019 in section three. Main findings from these analyses and additional research in the form of literature reviews and stakeholder feedback lead to policy recommendations for further tourism development that can be implemented in the short and medium term in section four.